Early childhood environmental education: A systematic review of the research literature - Ardoin, Nicole M.; Bowers, Alison W. (Educational Research Review, 2020)
Environmental education focused on the early-childhood years is experiencing dynamic growth in research and practice due to persistent environmental challenges coupled with burgeoning interest in the documented benefits of nature-rich experiences for infants and children. To better understand the landscape of early childhood environmental education (ECEE) pedagogical practices and expected outcomes, we undertook a systematic review of empirical studies of ECEE programs. Focusing on a 25-year span, we surfaced 66 studies that met our inclusion criteria. We found that participants in such programs spanned the early-childhood age range (birth through age eight) with the majority involving three- to six-year-olds in teacher-led, formal (school-like) programs. The primary outcomes documented in our sample studies included environmental literacy development, cognitive development, and social and emotional development. To a lesser extent, the studies addressed physical development and language and literacy development. On balance, our sample of ECEE studies reported strongly positive findings associated with the aforementioned outcomes. The majority emphasized the effectiveness of play-based, nature-rich pedagogical approaches that incorporated movement and social interaction. We include a visualization that synthesizes cross-sample findings with the intention of assisting ECEE practitioners in developing, implementing, and evaluating programs as well as encouraging researchers to further study elements, processes, and theoretical assumptions inherent in them.
Keywords: Early childhood; Environmental education; Forest schools; Nature preschools; Systematic reviews